Great Unexpectations - Gaventa, William C. (Journal of religion, disability & health, 2011)
A sermon by Bill Gaventa, reflecting on the ways that occasional unusual and unexpected actions by people with disabilities challenge our preconceptions and expectations based on the label of disability, and illustrate the Biblical ways in which God is revealed in unexpected people, in unexpected places and unexpected ways.